Kemas Ulang Informasi Masjid Tuo Kayu Jao Kabupaten Solok dalam Bentuk E-Book - Yulianti, Rita; Marlini, Marlini (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2019)
AbstractThis paper discusses the repackaging of information on Tuo Kayu Jao Mosque, Solok Regency in the form of e-books. The purpose of this paper is to describe the repackaging of information on the Tuo Kayu Jao Mosque in Solok Regency in the form of an e-book. In this paper the research method used is descriptive method by collecting data through direct interviews with one person in charge of the Tuo Kayu Jao Mosque, Solok Regency. Based on the discussion it can be concluded that the stages of repackaging information on the Tuo Kayu Jao Mosque in Solok Regency in the form of e-books are as follows: (1) identification of user needs, namely identifying user needs by interviewing visitors to the Tuo Kayu Jao Mosque; (2) information gathering and selection of information sources, i.e. gathering information can be obtained from the interview process with one administrator of the Tuo Kayu Jao Mosque and articles; (3) information packaging, i.e. the packaging of this information is made in the form of electronic books or e-books using Microsoft Word 2007 for editing and rendering into pdf forms; (4) determine the target audience, the target of the writer for the repackaging product information of Tuo Kayu Jao mosque, namely visitors and students who conduct research; (5) establishes the way information is disseminated by uploading products to the internet so that information users can easily access it; (6) transferring information, repackaging products of Tuo Kayu Jao Mosque, Solok Regency in the form of e-books can be transferred to floppy disks, CD-RWs, CD-ROMs, flasdisk to disseminate information; (7) evaluation of the product and the manufacturing process starts from making a writing framework such as a cover, preface, table of contents, content of the discussion and closing.Keywords: information packaging, mosque, e-book.